A temperature field superposition method for predicting the thermal behavior of lithium-ion battery. (November 2021) - He, Yi; Huang, Qiqiu; Tang, Xianwen; Li, Xinxi; Zhang, Guoqing; Wang, Changhong; Li, Canbing
Highlights: Temperature field superposition method is feasible in solving solid temperature field. The complex analysis process of differential equation for solving battery temperature variation is simplified by mathematical analytic method. The analytical solution to surface temperature variation of battery can be obtained through temperature field superposition method. The temperature field superposition analytical solution agrees very well with the experimental results. Abstract: In order to improve the working performance of the lithium-ion battery in continuous charge-discharge process, in this study, the temperature field superposition method has been proposed to investigate the temperature response of the lithium-ion battery, which was based on the results of the thermal properties and the temperature dropping measurements, aiming to deeply analyze the thermal behavior of battery. The feasibility of the estimation of temperature field superposition method in temperature response of prismatic LiFePO4 battery has been verified firstly by comparing on surface temperature with experiments. Furthermore, the battery with composite phase-change materials (CPCM) has also been selected to demonstrate the practicability of temperature field superposition method. It could be induced that the differences between numerical and experimental results were consistency, which were both below 2 °C under the condition of 1 C, 3 C or 5 C discharging rate. Therefore, it can be concluded that the temperature field superposition method could not only evaluate the surface temperature response of the battery but also predict the thermal behavior accurately, rapidly and simply, which would effectively improve the thermal safety performance of battery.